ANALISIS DEBIT DRAINASE DI RAWA PASANG SURUT HUTAN TANAMAN INDUSTRI (HTI) DI OGAN KOMERING ILIR (OKI) SUMATERA SELATAN - Zuchri, Rosmina; Setiawan, Budi Indra; Setyawan, Dwi; Soewarso, Soewarso (Indonesia University of Education, 2011)
The net of canal and control water building are needed in achieving and improving the result production of woods industrial forest furthermore for economic national development and social property. The canal constructing is important for debit fluctuation in canal drainage in order for continuities of water resources in wetland area. The purpose of this research 1) determined debit of drainage and presentation cross section as picture and formula rating curve, 2) analyzed fluctuation drainage of debit as the result of water level HOBO measurement, this research was done in tidal wetland at industrial wood forest OKI, South Sumatera. The way in getting the fluctuation modelling for debit of drainage was using a computer program which is known as Cubic Spline Interpolation (CSI). This program was used for picturing the profil cross section which is presented in rating curve as the result of measurement distance, deep canal and flow velocity as the input. As the result of this research, the width of canal drainage is about 8-10 m with deep 3- 4 m. Debit downstream is about 6,044 m3/second. and upstream 7,866 m3/second Rating curve is Qw=a. Hw^b, where Qw is debit (mÂ³/ second) and Hw is high of water from datum canal (m). The measurement of water level in canal drainage use Hobo data logger, the we used formula rating curve. Debit downstream max 9,311 m3/second and water level 3,110 m, min 0,129 m3/s and water level 0,270 m, at upstream of debit max 7,017 m3/s and water level 2,823 m. min 0,099 m3/s and water level 0,227 m.Key word: tidal lowland, cubic spline interpolation, rating curve. industrial woods forest.